Alda-1 Attenuates Hyperoxia-Induced Acute Lung Injury in Mice - Sidramagowda Patil, Sahebgowda; Hernández-Cuervo, Helena; Fukumoto, Jutaro; Krishnamurthy, Sudarshan; Lin, Muling; Alleyn, Matthew; Breitzig, Mason; Narala, Venkata Ramireddy; Soundararajan, Ramani; Lockey, Richard F.; Kolliputi, Narasaiah; Galam, Lakshmi (Frontiers in Pharmacology, 2021)
Acute lung injury (ALI), a milder form of acute respiratory distress syndrome (ARDS), is a leading cause of mortality in older adults with an increasing prevalence. Oxygen therapy, is a common treatment for ALI, involving exposure to a high concentration of oxygen. Unfortunately, hyperoxia induces the formation of reactive oxygen species (ROS) which can cause an increase in 4-HNE (4 hydroxy 2 nonenal), a toxic byproduct of lipid peroxidation. Mitochondrial aldehyde dehydrogenase 2 (ALDH2) serves as an endogenous shield against oxidative stress-mediated damage by clearing 4-HNE. Alda-1 [(N-(1, 3 benzodioxol-5-ylmethyl)-2, 6- dichloro-benzamide)], a small molecular activator of ALDH2, protects against ROS-mediated oxidative stress by promoting ALDH2 activity. As a result, Alda-1 shields against ischemic reperfusion injury, heart failure, stroke, and myocardial infarction. However, the mechanisms of Alda-1 in hyperoxia-induced acute lung injury (HALI) remains unclear. C57BL/6 mice implanted with Alzet pumps received Alda-1 in a sustained fashion while being exposed to hyperoxia for 48 hours. The mice displayed suppressed immune cell infiltration, decreased protein leakage and alveolar permeability compared to controls. Mechanistic analysis shows that mice treated with Alda-1 also experience decreased oxidative stress and enhanced levels of p-AKT and mTOR pathway associated proteins. These results show that continuous delivery of Alda-1 protects against hyperoxia-induced lung injury in mice.